Policy issues confronting Australian urban water reuse. Issue 4 (3rd July 2016) - Horne, James
Abstract: Urban water security in Australia's major cities is now very high, reflecting in part recent policy interventions. Important indirect potable water reuse projects were completed but no direct potable reuse project was undertaken and none seems likely in the near term. Governments have much to learn from decisions to build very large desalination and recycling plants, particularly around timing and scale. Future water reuse decisions are likely to have a much greater commercial focus. Policies and regulations giving more flexibility to decentralized provision of water-related services could result in further growth of climate-resilient water resources and non-potable reuse.